Media Sosial dan Pengaruhnya terhadap Pembentukan Identitas Diri Remaja di Kelas XII SMAN 1 Kota Langsa - Rodia Afriza; Rahmat Syaibani; Ikhbal Hidayat Lubis; Nur Anzelina Hrp; Abdul Halim; Lisa Sundari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The development of social media is currently very rapid and diverse, such as Whatsapp, YouTube. The existence of social media, especially among young people, has given rise to a diversity of uses and images of the identities of its users. Based on the background above, the following problem formulation arises, How do teenagers behave in interpreting the social media Instagram within themselves. And how is the use of Instagram social media in forming self-identity related to social interaction in society. In this discussion the theory used is symbolic interaction theory, where this theory focuses its attention on the ways humans use to shape the meaning and structure of society through conversation. Quoted from George Herbert Mead Symbolic interaction is a theory about how to think about the mind and self. This research uses a qualitative approach with a descriptive case study method. Data was collected through in-depth interviews, observation and literature study. Research subjects were selected (purposively) based on the characteristics of being active users, having more than one account, aged 16-18 years, and consisting of men and women. The research results show that there is diversity in the use of social media, this can be seen from the initial use, patterns of use and the technology used. Then there are various meanings regarding the existence of social media for users, including those related to themselves, family, studies, hobbies, community and work. After that, there are various meanings regarding the self-identity of social media users, and identity construction on social media is carried out through the process of interaction in using social media.